LOW POWER DC/DC CONVERTER FROM 3 KV TO 300 V – SIMULATION ANALYSIS - Matelski, Wojciech (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
The article presents a 150 W converter, supplied from the railway 3 kV DC traction grid, lowering the voltage to a level of 300 V. The described structure enables the selection of low cost IGBT devices. A parallel connection of five identical two-transistor flyback converters, with division of input voltage on a series of capacitors, has been proposed. The operation of converter, together with the developed control method, has been tested by performing simulation studies. In states of input voltage variations, the converter powers the load with stable output voltage.